Catalytic pyrolysis of 5-Amino-1H-Tetrazole with copper and its oxide: A deep insight into the combustion mechanism for high nitrogen compound. (15th February 2023) - Zhou, Si-Yuan; Chen, Jiu; Li, Xuan; Jia, Fan; Zhang, Dan; Xie, Li-Feng; Li, Bin; Jiang, Lin
Graphical abstract: Highlights: By recrystallization method, Cu and CuO are combined with a new material, 5AT. Pyrolysis models for 5AT in each stage are deduced by Coats-Redfern method. 5AT can undergo isomeric interconversion in the presence of metal catalysts. The overall catalytic effect of copper is superior to that of copper oxide. Abstract: As a new amino tetrazole compound, 5-Amino-1H-Tetrazole (5AT) has been widely used in propellants, blunt explosives, and airbags considering its advantages as high gas yield, environmentally friendly product, and low allergenicity. Yet, deficiencies such as wide pyrolysis range and low ignition temperature still exist in 5AT. So it is necessary to take some measures to improve its performance. Metal oxides and metals have been well established as catalysts in the field of energy-containing materials. In order to investigate the effect of Cu elements on the performance of 5AT pyrolysis, Cu and CuO are selected as catalysts for comparative analysis in this paper. It is found that the second stage of 5AT pyrolysis disappears in the presence of the catalysts, leaving only two stages. The activation energy of 5AT is reduced by about 30 kJ/mol and the pyrolysis model remains unchanged (still the F2 model) for the first stage. This indicates that the catalysts have a minimal effect on the first stage of 5AT. Due to the lower activation energy of 5AT-Cu and the SEM-EDS results showing that Cu is more tightly bound to 5AT, it could be inferred that Cu is more effective than CuO in the first stage. For the third stage, the activation energy of 5AT is reduced by the catalyst over 100 kJ/mol, with the pyrolysis model changing from F1 to D3, suggesting that the catalysts mainly act in the third stage. Since the activation energy of 5AT differs by no more than 3 % between the two catalysts, the pyrolysis model remains the same (both are D3). That means that the effects of the two catalysts are compatible. In terms of overall effectiveness, the effect catalyst Cu is superior to CuO. This paper can provide a reference for the choice of catalyst type, compounding method as well as the further combustion process of 5AT.